The impact of inflation, exports, and corruption perception on the movement of the Chinese Yuan Exchange Rate in selected ASEAN countries in the short and long run - Muhammad Ahnaf Fauzan; Enos Adryansyah Gumilang; Dijan Rahajuni; Rinny Apriliany Zakaria (Privietlab, 2026)
This study examines how inflation, exports, and corruption perception influence the movement of Chinese Yuan (CNY) against the currencies of Indonesia, Malaysia, and Vietnam. Using a Panel Autoregressive Distributed Lag model with annual data from 2013 to 2023, the analysis captures both the short-term adjustments and the long-term equilibrium relationships among the variables. The results show that export performance plays the most decisive role in the short term. Stronger export activity is associated with an appreciation of the Yuan against ASEAN currencies, reflecting the increasingly interconnected trade structure between China and the region. Inflation and corruption perceptions do not have significant short-term effects. Their influence tends to appear gradually through channels such as investor confidence, institutional stability, and the overall macroeconomic environment of the country. Although these variables do not show immediate statistical significance, the cointegration tests confirm the presence of a stable long-run relationship between the exchange rate and explanatory variables. Taken together, the findings highlight that trade remains the primary force shaping short-term exchange rate behavior in ASEAN. Simultaneously, institutional quality and price stability continue to serve as important foundations for maintaining long-run external resilience. These results emphasize the need for stronger economic structures and credible governance so that ASEAN currencies are better positioned to withstand external pressures arising from China’s expanding role in regional economic activity.